Research and Design of Intelligent Substation of Assist Control System Based on Internet of Things and Three-Dimensional Visualization Technology - Sirui Pang; Hongfei Xu; Jianwen Du; Xuemei Li (Dianxin kexue)
With the rapid development of the internet of things and three-dimensional visualization technology，the intelligent substation of assist control system based on internet of things and three-dimensional visualization technology is one of the most popular research issues. The intelligent substation architecture was introduced，and the design and function of intelligent substation of assist control system were proposed. It provided a reference for operation and management of intelligent substation.